Presence of Induced Weak Ferromagnetism in Fe-Substituted YFexCr1−xO3 Crystalline Compounds - Roberto Salazar-Rodriguez; Domingo Aliaga Guerra; Jean-Marc Greneche; Keith M. Taddei; Noemi-Raquel Checca-Huaman; Edson C. Passamani; Juan A. Ramos-Guivar (Nanomaterials, 2022)
Fe-substituted YFexCr1−xO3 crystalline compounds show promising magnetic and multiferroic properties. Here we report the synthesis and characterization of several compositions from this series. Using the autocombustion route, various compositions (x = 0.25, 0.50, 0.6, 0.75, 0.9, and 1) were synthesized as high-quality crystalline powders. In order to obtain microscopic and atomic information about their structure and magnetism, characterization was performed using room temperature X-ray diffraction and energy dispersion analysis as well as temperature-dependent neutron diffraction, magnetometry, and 57Fe Mössbauer spectrometry. Rietveld analysis of the diffraction data revealed a crystallite size of 84 (8) nm for YFeO3, while energy dispersion analysis indicated compositions close to the nominal compositions. The magnetic results suggested an enhancement of the weak ferromagnetism for the YFeO3 phase due to two contributions. First, a high magnetocrystalline anisotropy was associated with the crystalline character that favored a unique high canting angle of the antiferromagnetic phase (13°), as indicated by the neutron diffraction analysis. This was also evidenced by the high magnetic hysteresis curves up to 90 kOe by a remarkable high critical coercivity value of 46.7 kOe at room temperature. Second, the Dzyaloshinskii–Moriya interactions between homogenous and heterogeneous magnetic pairs resulted from the inhomogeneous distribution of Fe3+ and Cr3+ ions, as indicated by 57Fe Mössbauer studies. Together, these results point to new methods of controlling the magnetic properties of these materials.